SISTEM PAKAR DIAGNOSIS PENYAKIT PADA BALITA DENGAN METODE FORWARD CHAINING - Tri Andi; Reska Mayefis (Maternal Child Health Care, 2022)
Children under the age of 1 year (toddlers) are more susceptible to disease, which causes the environment to greatly affect the health of toddlers. Children's health is one of the most important things, especially when the child is in its infancy. The importance of SOP is one of the assessments of the quality of health services for both government and private agencies. There is input from patients as service users so that the importance of SOP for General Hospital services as service guidelines so that patient satisfaction is obtained. The purpose of this study was to see how useful the SOPs were compiled and the compliance of doctors in providing services based on SOPs on the quality of service received by patients. The method used is the Forward Chaining Method which is a method for reasoning from a problem by providing a solution. This research is an applied technology product that is expected to provide benefits as a media for consultation or instructor for the community in general, as well as for doctors and paramedics at public hospitals. The design of this system has been carried out through data collection activities, design rules, process design and system testing. From the collection of data and information found disease facts, complaints, symptoms and suggestions for treatment. The results obtained from testing the system using the PHP MySQl application show that the results of diagnoses and diseases of children at Tanjung Balai General Hospital have as many as 10 patient data that have been studied by experts and have carried out system testing to achieve an accuracy of 80%. Keywords: SOP, Forward chaining, rules, PHP MySQl, Expert System, disease diagnosis.